PREVALENCE OF HEALTH PROBLEMS AMONG MENOPAUSAL WOMEN AND ASSESSMENT OF THEIR QUALITY OF LIFE: A COMMUNITY-BASED STUDY IN WESTERN ODISHA - MONIKA SATPATHY*; CHANDRASHREE LENKA (The Journal of Research ANGRAU, 2020)
Menopause is a natural phenomenon in every of women’s health. The descriptive cum exploratory research study was carried out in western Odisha among 330 rural, urban, and tribal women in the age group of 35-55 years, from April to September of 2018. Purposive sampling method was used to select the respondents. The findings of the study revealed that the mean menopausal age was 46.22±4.39 years. The most common symptoms reported by the women were irritability, physical and mental exhaustion (63%) and depression (56.96%). Hot flashes and night sweats were also found in 61.51% of the respondents, whereas, joint pain and muscular pains were found in 66.06% of women. Urogenital problems like bladder problems and dryness of the vagina were found among 59.39% and 35.45% respondents, respectively. However, a statistically significant association was found in the prevalence of menopausal symptoms and their degree of severity with menopausal status, and current age of menopausal women in this study which ultimately affects the quality of life of the menopausal women.